Plant Leucine Aminopeptidases Moonlight as Molecular Chaperones to Alleviate Stress-induced Damage - Scranton, Melissa A. (American Society for Biochemistry and Molecular Biology, 2012)
Leucine aminopeptidases (LAPs) are present in animals, plants, and microbes. In plants, there are two classes of LAPs. The neutral LAPs (LAP-N and its orthologs) are constitutively expressed and detected in all plants, whereas the stress-induced acidic LAPs (LAP-A) are expressed only in a subset of the Solanaceae. LAPs have a role in insect defense and act as a regulator of the late branch of wound signaling in Solanum lycopersicum (tomato). Although the mechanism of LAP-A action is unknown, it has been presumed that LAP peptidase activity is essential for regulating wound signaling. Here we show that plant LAPs are bifunctional. Using three assays to monitor protein protection from heat-induced damage, it was shown that the tomato LAP-A and LAP-N and the Arabidopsis thaliana LAP1 and LAP2 are molecular chaperones. Assays using LAP-A catalytic site mutants demonstrated that LAP-A chaperone activity was independent of its peptidase activity. Furthermore, disruption of the LAP-A hexameric structure increased chaperone activity. Together, these data identify a new class of molecular chaperones and a new function for the plant LAPs as well as suggesting new mechanisms for LAP action in the defense of solanaceous plants against stress.